Health benefits of algal polysaccharides in human nutrition - Mišurcová, Ladislava; Škrovánková, Soňa; Samek, Dušan; Ambrožová, Jarmila; Machů, Ludmila (Advances in food and nutrition research, 2012)
The interest in functional food, both freshwater and marine algal products with their possible promotional health effects, increases also in regions where algae are considered as rather exotic food. Increased attention about algae as an abundant source of many nutrients and dietary fiber from the nutrition point of view, as well as from the scientific approaches to explore new nutraceuticals and pharmaceuticals, is based on the presence of many bioactive compounds including polysaccharides extracted from algal matter. Diverse chemical composition of dietary fiber polysaccharides is responsible for their different physicochemical properties, such as their ability to be fermented by the human colonic microbiota resulted in health benefit effects. Fundamental seaweed polysaccharides are presented by alginates, agars, carrageenans, ulvanes, and fucoidans, which are widely used in the food and pharmaceutical industry and also in other branches of industry. Moreover, freshwater algae and seaweed polysaccharides have emerged as an important source of bioactive natural compounds which are responsible for their possible physiological effects. Especially, sulfate polysaccharides exhibit immunomodulatory, antitumor, antithrombotic, anticoagulant, anti-mutagenic, anti-inflammatory, antimicrobial, and antiviral activities including anti-HIV infection, herpes, and hepatitis viruses. Generally, biological activity of sulfate polysaccharides is related to their different composition and mainly to the extent of the sulfation of their molecules. Significant attention has been recently focused on the use of both freshwater algae and seaweed for developing functional food by reason of a great variety of nutrients that are essential for human health.
Keywords: Cyanobacteria; sinice; Dietary Fiber; Global Health; polysacharidy; celosvětové zdraví; Phaeophyceae; lidé; Chlorophyta; dieta; mořské řasy; Diet; funkční potraviny; Rhodophyta; Functional Food; Seaweed; Polysaccharides; potravní vláknina; Humans